Facile synthesis and photocatalytic activity of Ag3PO4 decorated MoS2 nanoflakes on carbon fiber cloth. (April 2018) - Cui, Zhe; Sun, Yangang; Zhang, Zhendong; Xu, Meilan; Xin, Binjie
Graphical abstract: A novel CC@MoS2 -Ag3 PO4 heterostructure is fabricated by a simple hydrothermal method and a successive ionic layer adsorption reaction, and displays a superior photocatalytic activity compared with CC@MoS2 heterostructure, which is more than 10 times as much as that of single pure Ag3 PO4 or MoS2 and will prompt their practical application to eliminate the pollutants. Highlights: A novel CC@MoS2 -Ag3 PO4 heterostructure is fabricated by a facile method. The growth process of CC@MoS2 is investigated. The heterostructure displays an excellent photocatalytic property. Cyclic Voltammetry is utilized to investigate the photocatalytic mechanism. Abstract: A novel CC@MoS2 -Ag3 PO4 heterostructure, composed of Ag3 PO4 nanoparticles decorated MoS2 nanosheets on carbon fiber cloth (CC), is fabricated by a simple hydrothermal method and a successive ionic layer absorption reaction. The CC@MoS2 -Ag3 PO4 heterostructure displays an excellent photocatalytic activity of ∼96% degradation rate for RhB solution under simulated daylight, which is more than 10 times as much as that of pure Ag3 PO4 or MoS2 . The CC@MoS2 -Ag3 PO4 heterostructure with optimized photoactivity is investigated by optical and electrochemical measurements. The CC@MoS2 -Ag3 PO4 heterostructure can not only broaden the photoresponse range of MoS2, but also alleviate the photodegradation of Ag3 PO4, and the easily separated CC provides a proper conductive substrate and rapid charge transfer channels. The probable photocatalytic mechanism of CC@MoS2 -Ag3 PO4 heterostructure is discussed in detail. Therefore, the CC@MoS2 -Ag3 PO4 heterostructure with high efficient photocatalytic performance and easy separation is a promising photocatalytic material.